2019
DOI: 10.1002/hpm.2752
|View full text |Cite
|
Sign up to set email alerts
|

Patient costs of hypertension care in public health care facilities in Kenya

Abstract: Summary Background Hypertension in low‐ and middle‐income countries, including Kenya, is of economic importance due to its increasing prevalence and its potential to present an economic burden to households. In this study, we examined the patient costs associated with obtaining care for hypertension in public health care facilities in Kenya. Methods We conducted a cross‐sectional study among adult respondents above 18 years of age, with at least 6 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 37 publications
4
61
2
Order By: Relevance
“…Similar findings have been reported by recent studies in Kenya and South Africa . Costs due to medicine have been shown to reduce adherence to medication and demand for health services by patients with NCDs . Past studies conducted in LMICs have however shown that social health insurance schemes do not comprehensively cover the costs for medicines and that OOP costs, which are majorly contributed by medicines, are a hindrance to attainment of universal health coverage in many low resource settings .…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been reported by recent studies in Kenya and South Africa . Costs due to medicine have been shown to reduce adherence to medication and demand for health services by patients with NCDs . Past studies conducted in LMICs have however shown that social health insurance schemes do not comprehensively cover the costs for medicines and that OOP costs, which are majorly contributed by medicines, are a hindrance to attainment of universal health coverage in many low resource settings .…”
Section: Discussionsupporting
confidence: 81%
“…This could be due to the differences in study population. However, we hypothesize the poorest individuals faces several nancial barriers, which hinder access to health services for control and treatment of hypertension [56] due to huge out of pocket expenditure [6,57]. In addition, despite the hypertension screening and early diagnosis being key in averting hypertension, it is likely that individuals in the richest wealth quintile are screened more for high blood pressure than the poorest individuals.…”
Section: Discussionmentioning
confidence: 96%
“…AMPATH’s CDM programme has lower average per visit costs compared to other public programs that offer chronic NCD care in Kenya, and substantially lower costs than hospitalizations related to untreated NCDs [33,34]. This difference should not disqualify the generalizability of our findings and recommends the expansion of the CDM programme.…”
Section: Discussionmentioning
confidence: 78%